Chlorine dioxide flushing protocols for microbial reduction in dental chair units - Julian Winkler; Susann Herzog; Felix Dahlhaus; Arndt Matschulat; Helmut Uhlmann; Alexander Mellmann; Thorsten Kuczius (PLoS ONE, 2026)
Dental chair unit (DCU) waterlines are often microbiologically contaminated. This poses infection risks for patients and dental staff if they are not regularly rinsed and disinfected. This clinical hygiene study evaluated chlorine dioxide (ClO₂) rinsing protocols for microbial and biofilm reduction in DCUs. Automated protocols were tested with varying ClO₂ concentrations and flushing frequencies. Flow cytometry and agar culturing were used to assess microbial load. Continuous low-dose rinsing (1.2 mg/L ClO₂) achieved sustainable microbial reduction (up to 2.51 log₁₀), whereas single high-dose shock disinfections (22.7 mg/L) resulted in transient reductions. ClO₂ was effective in biofilm removal, but its depletion during stagnation highlights the need for continuous application. ClO 2 seems to be a suitable disinfectant for removing both microbiological contamination and biofilms of DCUs; however, depletion effects of active ClO 2 were evident underlining the importance of a stable permanent ClO 2 application. Our results prove that permanent low-dose ClO 2 application of DCU waterlines is recommended for sustainable water disinfection. A high-concentrated shock disinfection on a periodically basis can be used for biofilm removal, which was demonstrated with experimentally grown biofilm of P. aeruginosa .